Association of Immune Thrombocytopenia and T-Lymphoblastic Lymphoma in a Pediatric Patient - Ryan A. Denu; Daniel R. Matson; Matthew J. Davis; Natalie J. Tedford; Christine E. Brichta; Carol A. Diamond; Margo L. Hoover-Regan (Case Reports in Hematology)
Immune thrombocytopenia (ITP) is characterized by isolated thrombocytopenia of unclear etiology. We present a unique case of an 8-year-old girl with chronic ITP who was subsequently diagnosed with T-lymphoblastic lymphoma at age 11. The clinical course was complicated by the occurrence of nonepileptiform events with bizarre behavior changes following the administration of nelarabine and intrathecal and high-dose systemic methotrexate. This case highlights an unusual co-occurrence of hematologic malignancy and chronic ITP in an otherwise healthy child. We speculate that underlying genetic or immunologic lesions may predispose a subset of pediatric ITP patients to the development of hematologic malignancies.